A cationic lipid with advanced membrane fusion performance for pDNA and mRNA delivery. Issue 10 (22nd February 2023) - Wei, Yu; He, Ting; Bi, Qunjie; Yang, Huan; Hu, Xueyi; Jin, Rongrong; Liang, Hong; Zhu, Yongqun; Tong, Rongsheng; Nie, Yu
Abstract : Cationic lipids were designed to study the structure–activity relationship of hydrophobic parts. At a certain length, the unsaturation degrees significantly affected the transgene expression through enhancing membrane fusion and fluidity. Abstract : The success of mRNA vaccines for COVID-19 prevention raised global awareness of the importance of nucleic acid drugs. The approved systems for nucleic acid delivery were mainly formulations of different lipids, yielding lipid nanoparticles (LNPs) with complex internal structures. Due to the multiple components, the relationship between the structure of each component and the overall biological activity of LNPs is hard to study. However, ionizable lipids have been extensively explored. In contrast to former studies on the optimization of hydrophilic parts in single-component self-assemblies, we report in this study on structural alterations of the hydrophobic segment. We synthesize a library of amphiphilic cationic lipids by varying the lengths ( C = 8–18), numbers ( N = 2, 4), and unsaturation degrees ( Ω = 0, 1) of hydrophobic tails. Notably, all self-assemblies with nucleic acid have significant differences in particle size, stability in serum, membrane fusion, and fluidity. Moreover, the novel mRNA/pDNA formulations are characterized by overall low cytotoxicity, efficient compaction, protection, and release of nucleic acids. We find that the length of hydrophobic tails dominates the formation and stability of the assembly. And at a certain length, the unsaturated hydrophobic tails enhance the membrane fusion and fluidity of assemblies and thus significantly affect the transgene expression, followed by the number of hydrophobic tails.